2011
DOI: 10.1039/c0ob01003k
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive detection of saccharides under physiological conditions with click synthesized boronic acid-oligomer fluorophores

Abstract: Two phenylboronic acid based saccharide sensors bearing conjugated oligomer fluorophores with linear and cruciform π-frameworks were synthesized in a modular approach utilizing a Cu-catalyzed alkyne azide cycloaddition (click) reaction. The cruciform fluorophore showed excellent saccharide sensing function under physiological conditions in the mM range, whereas the linear fluorophore gave very limited sensing functions. The different fluorescent sensing behaviours highlight the important role of oligomer fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 46 publications
(7 reference statements)
0
21
0
Order By: Relevance
“…26 Herein, titrations of 1a and 1c with fructose were studied by 1 H NMR spectroscopy, following the protocol of Mulla et al 19 These two compounds were selected in order to compare the effect of a potential triazole-boronic acid interaction on fructose binding. 26 Herein, titrations of 1a and 1c with fructose were studied by 1 H NMR spectroscopy, following the protocol of Mulla et al 19 These two compounds were selected in order to compare the effect of a potential triazole-boronic acid interaction on fructose binding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Herein, titrations of 1a and 1c with fructose were studied by 1 H NMR spectroscopy, following the protocol of Mulla et al 19 These two compounds were selected in order to compare the effect of a potential triazole-boronic acid interaction on fructose binding. 26 Herein, titrations of 1a and 1c with fructose were studied by 1 H NMR spectroscopy, following the protocol of Mulla et al 19 These two compounds were selected in order to compare the effect of a potential triazole-boronic acid interaction on fructose binding.…”
Section: Resultsmentioning
confidence: 99%
“…1b). 19 Their computational study revealed a solvent insertion using the central nitrogen of the triazole. The postulate of a triazole to boronic acid interaction was further investigated in a separate study by Mulla et al with supporting computational analysis (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained borio-lithio derivatives can be easily converted into various functionalized arylboronic acids that can be used in coupling reactions [10,11] or tested as saccharides sensors. [12,13] …”
Section: Introductionmentioning
confidence: 98%
“…However, significant enhancement of fluorescence is observed upon reaction of the boronic acid with 1,2 diols of saccharides to form complex (II), which has been proposed to involve donation of electronic charge to boron from nitrogen, [4], thus inhibiting any PET process. Theoretical investigations on model systems have been devoted mainly to the elucidation of the interaction between B and N in these sensors [7][8][9][10] and determination of the most stable conformer of the sensors and as shown in (I) structures involving intramolecular B-O-HÁ Á ÁN interaction are found to be generally lower in energy than those involving a B-N bond [7][8][9]. Inference on the photoinduced electron transfer capabilities and fluorescence properties of protonated and neutral sensor systems has been made on the basis of electron-density plots of the highest occupied (HOMO) and the lowest unoccupied molecular orbitals (LUMO) of protonated and neutral sensors molecules [11].…”
Section: Introductionmentioning
confidence: 99%